Production of low cost feminine hygiene from kenaf - Wong, Wei Ding (2014)
Kenaf has been discovered for its potential in different kinds of industrials such as paper making, manufacturing materials, sanitary products and tissues. Kenaf is known as the most economical crop. The present exist of feminine hygiene product are produced by high cost chemicals. This may cause to increase the price. Lots of women in the developing countries still do not have enough supply of cheap feminine hygiene product and this force them use unhygienic materials such as rags, barks and even mud. So there is a need in invention and manufacturing of low cost sanitary product. This research is to analyse the best method for the production of low cost feminine hygiene from kenaf by using suitable mechanical and chemical method. Application of acidic, alkaline and hypochlorite treatment in the pulping process will increase the quality of fluff pulp without affect its basic fibre properties. The raw material of kenaf is supply by National Kenaf and Tobacco Board, Kuantan Branch. Mechanical separation was done to remove the outer bast fiber of kenaf manually. In this study, Sodium Sulphite, Glacial Acetic acid and sodium hypochlorite was used in the production of pulp as it is low cost and suitable for treating core fibres. All the samples were sent for FESEM and SEM scanning to investigate the morphological condition of the pores of the fibres for the sample. Absorbency test was carried out for each sample. The absorbency of each sample includes untreated and treated samples are higher than 1.00 g of ink/g of ink/g of sample as shown in table 1. Samples treated with 20% Glacier Acidic acid show lowest absorbency with 1.08 g of ink/g of sample. Samples treated with 1 g of sodium sulphite showed quite high absorbency at 1.836 g of ink/g of sample. The treated sodium sulphite kenaf core pores are porous and there is increasing in the absorbency characteristics. Furthermore, EDS FESEM analysis shown elementary composition contains inside samples without any sulphur remained in sodium sulphite treated sample